Pengaruh E-Commerce dan Modal Usaha terhadap Pendapatan Pedagang Tradisional di Pasar Gang Siku Kota Jambi - Nadia Nurmusischa; Bambang Kurniawan; Beid Fitrianova Andriani (ARZUSIN, 2025)
The decline in income among traditional market traders at Pasar Gang Siku, Jambi City, due to the growing dominance of e-commerce and limited business capital forms the background of this study, while research simultaneously examining both factors remains limited. This study aims to analyze the influence of e-commerce utilization and business capital on the income of traditional clothing traders at Pasar Gang Siku within the context of the digital era. A quantitative approach was employed, with random sampling applied to 65 clothing traders. Data were analyzed using multiple linear regression tests. The results indicate that e-commerce has a significant effect on traders' income, with a significance value of 0.001 and a regression coefficient of 0.470. Conversely, business capital does not have a significant partial effect, with a significance value of 0.052 and a regression coefficient of 0.211. However, both variables together significantly influence traders' income. The study concludes that e-commerce utilization is a key factor in increasing traditional traders' income amidst digital transformation, while the effectiveness of business capital depends on managerial capacity and technological adaptation. The implications include a theoretical contribution to the study of traditional market adaptation in the digital age and practical recommendations for formulating digital-based local economic empowerment strategies.